Total synthesis of integrastatin B enabled by a benzofuran oxidative dearomatization cascade - More, Atul A.; Ramana, Chepuri V. (Organic Letters, 2016)
The first total synthesis of integrastatin B, a potent HIV-1 integrase inhibitor, has been accomplished in seven steps with a 17.9% overall yield employing easily accessible starting compounds. The Oxone-mediated oxidative benzofuran dearomatization cascade has been employed as the key skeletal construct to forge the central tetracyclic nucleus.